Women's trajectories of postpartum depression and social support: A repeated‐measures study with implications for evidence‐based practice. Issue 2 (12th January 2022) - Lee, Li‐Chun; Hung, Chich‐Hsiu
Abstract: Background: Postpartum depression is one of the most common psychological disorders of women after childbirth. Despite the importance of social support as an influencing factor, there have been few studies on the trends and characteristics of social support as it relates to postpartum depression. Aims: To explore the trends in postpartum depression and social support, to cross‐analyze the correlation between the postpartum depression trajectory and the social support trajectory, and to investigate predictors of changes in postpartum depression trajectories. Methods: A prospective repeated‐measure study and convenience sampling were used to recruit 230 women at 1, 3, and 6 months after childbirth. Structured questionnaires were used for data collection. Trajectory analysis was used to explore the trajectories of postpartum depression and social support during the 6 months after childbirth, and polynomial logistic regression was used to explore predictors of the trajectory of postpartum depression. Results: Postpartum depression was at its most serious in the third month after childbirth, showing patterns of low‐risk, moderate‐risk, and high‐risk trajectories. Social support also showed low, moderate, and high patterns, and the trajectory of postpartum depression was significantly related to the trajectory of social support. The predictors of moderate‐risk and high‐risk postpartum depression were also found in this study. Linking Evidence to Action: Postpartum mental health education and online learning systems should be used to increase social support for women after childbirth and reduce the incidence of postpartum depression.